Prison overcrowding and recidivism : evidence from an expansion in prison capacity (2016)
I investigate the relationship between prison overcrowding and recidivism by focusing on the rearrest rates of inmates exposed to different levels of overcrowding. To do so, I exploit an exogenous variation in overcrowding levels suffered by inmates resulting from an expansion of about 25 thousand slots in the Colombian penitentiary systm. Since 2004 and up to 2013 some prisons were expanded and others built. Results for the intention to treat show that inmates at treated prisons are between 0.6 and 1 percentage point less likely to be rearrested the same calendar year of release (i.e. 30% to 50% relative to the average rearrest rate). The local effect for inmates who actually saw a change in overcrowding shows that a one standard deviation increase in the overcrowding level (i.e. 67.1 percentage points or 94% relative to the mean), causes an increase of 1.4 percentage points in the likelihood of rearrest in the same calendar year of the inmate's release (i.e. 70% relative to the average rearrest rate). This effect seems to be driven by a limitation to enroll into rehabilitation programs.